Gold dinar as a consumer product: modified version of the theory of planned behaviour - Peredaryenko, Margarita Sergeevna (Kulliyyah of Economics and Management Sciences, International Islamic University, Malaysia., 2019)
This study is a conceptual discussion that explores the literature concerning the purchase intention of the gold dinar in Malaysia. Although some research has been done on gold dinar acceptance in the past, a thorough marketing research perspective has been missing in this niche. Yet the gold dinar market is quite dynamic with many public and private initiatives yielding mixed response from the public. The literature suggests that the theory of planned behaviour (TPB) is a good analytical approach to understand the purchase intention of Malaysian customers. However, the author of this theory, Ajzen, has discarded the construct of knowledge as irrelevant to the process of formationof behavioural intention. On the other hand, the competing cognitive behavioural theories postulate knowledge as an important variable, at least in the context of consumer behaviour. Thus, this study proposes a modified version of the TPB that includes objective product knowledge and subjective productive knowledge as exogeneous variables. A conceptual framework is presented with attitude and perceived behavioural control as mediators. A total of 16 hypotheses were generated. Fresh marketing behavioural perspective and consumer knowledge inclusion offers new and potentially more insightful avenues for understanding public behaviour towards gold dinar by academics and practitioners.